2006
DOI: 10.1080/07373930601030747
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Model for the Model-Based Control of a Biofuel Dryer at an Industrial Combined Heat and Power Plant

Abstract: The primary aim of this article is to present a simulation model for a bark dryer integrated into a combined heat and power plant. The same model can be used for the model-based control of the dryer. The secondary aim is to evaluate how useful the control is from an economic point of view. Results show that the final fuel moisture content can be stabilised by controlling the drying temperature(s). On the other hand, the deviation in final bark moisture decreases even when the dryer has no control at all. Net i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Some authors have reported on the simulation of biomass kiln dryers over the past decades. Prominent amongst them include Steinmann, [24], Holmberg and Ahtila [25], and Eriksson et al [26]. Steinmann [24], in his years of experience, developed a real-time simulation system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported on the simulation of biomass kiln dryers over the past decades. Prominent amongst them include Steinmann, [24], Holmberg and Ahtila [25], and Eriksson et al [26]. Steinmann [24], in his years of experience, developed a real-time simulation system.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations agreed reasonably well with the experimentally measured values. Holmberg and Ahtila [25], modeled the bark drying process in a continuous cross-flow dryer. The model included the use of secondary heat sources from plants for dry air heating.…”
Section: Introductionmentioning
confidence: 99%